1998
DOI: 10.1097/00005768-199805001-01745
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Exercise and Training on Muscle Lipid Metabolism

Abstract: . Evaluation of exercise and training on muscle lipid metabolism. Am. J. Physiol. 276 (Endocrinol. Metab. 39): E106-E117, 1999.-To evaluate the hypothesis that endurance training increases intramuscular triglyceride (IMTG) oxidation, we studied leg net free fatty acid (FFA) and glycerol exchange during 1 h of cycle ergometry at two intensities before training [45 and 65% of peak rate of oxygen consumption (V O 2 peak )] and after training [65% pretraining V O 2 peak , same absolute workload (ABT), and 65% post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 23 publications
9
78
1
Order By: Relevance
“…In accordance, improvements in insulin sensitivity following resistancetype exercise training (27)(28)(29) have been shown to occur independent of structural changes in skeletal muscle and/ or IMCL and/or glycogen contents (33). Previous studies have either reported no change (76)(77)(78), a decrease (79) or even an increase (80,81) in IMCL content after exercise training. As such, we expand on previous findings that the reported improvements in physical fitness, muscle strength as well as the attenuated rise in EIR are not necessarily accompanied by significant changes in muscle fibre-type characteristics, MUOX and/or muscle lipid and/or glycogen content.…”
Section: Discussionmentioning
confidence: 66%
“…In accordance, improvements in insulin sensitivity following resistancetype exercise training (27)(28)(29) have been shown to occur independent of structural changes in skeletal muscle and/ or IMCL and/or glycogen contents (33). Previous studies have either reported no change (76)(77)(78), a decrease (79) or even an increase (80,81) in IMCL content after exercise training. As such, we expand on previous findings that the reported improvements in physical fitness, muscle strength as well as the attenuated rise in EIR are not necessarily accompanied by significant changes in muscle fibre-type characteristics, MUOX and/or muscle lipid and/or glycogen content.…”
Section: Discussionmentioning
confidence: 66%
“…This is probably explained by the fact that TG, stored in deep AT, first has to be hydrolyzed into FFA and then transported from the AT to the site of oxidation (mitochondrion) within the muscle fiber. Exercise training often 3,33,34 but not always 35 increases the amount of muscle TG. In accordance with the positive correlation found in the present study between VO 2max and FATOX max (Table 2), endurance training also increases fat oxidation rate during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exercise training on TG m content in healthy subjects are equivocal, with some studies reporting an increase [11,24,25], decrease [26] or no [9,10,27] after short-term (6-12 weeks) endurance exercise. In our investigation, exercise training had little effect on TG m concentrations in control subjects, but resulted in a substantial overall decrease in patients with Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%